Experimental investigation of GO-HPAM and SiO2-HPAM composite for cEOR: Rheology, interfacial tension reduction, and wettability alteration - Kumar, D. (Elsevier B.V., 2022)
The interest in designing and developing polymeric nanoparticles has grown in recent years. The inclusion of nanoparticles in polymer solutions enhances several properties, such as stability, rheological and shear characteristics, polymer adsorption, wettability alteration, and so on, leading to increased oil recovery. Graphene oxide (GO) nanosheets and Aerosil 300 Silica oxide (SiO2) are the superior nanoparticles because of their robust thermal and mechanical properties. However, a systematic study of the use of GO and SiO2 in hydrolyzed polyacrylamide (HPAM) has not been reported. The present research seeks to improve the stability of nanoparticles, the rheological characteristics of polymeric nanofluids, and to understand the functional interaction of nanoparticles in reducing interfacial tension and altering wettability. The nano polymer composites were characterized by Fourier-transform infrared spectroscopy and scanning electron microscopy. The samples were treated with NaCl (30,000 mg/L) and CaCl2 (1000 mg/L) brine solutions at 25 °C and 80 °C. The findings indicated that the addition of GO and SiO2 into HPAM significantly improves rheological properties, reduced IFT, and decreased contact angle. GO performs better than SiO2 in terms of better rheological properties and the reduction of IFT. However, the use of SiO2 in HPAM resulted in a lower contact angle in comparison to GO-HPAM nano-polymeric solution. The synergetic effect of GO and SiO2 with HPAM showed promising results under harsh reservoir conditions and hence can be considered as a good candidate for the application of chemical enhanced oil recovery. © 2022 Elsevier B.V.